Рассказы русских писателей - Подивилова Ольга Васильевна (Школьная библиотека, 2016)
Экземпляры: (20221011) / Инвентарный номер: 41851 / Цена: 97.00 / Сис.шифр: 84(2=411.2) / Авт.знак: Р 24 / ГРНТИ: 17.82 / ББК: 84(2=411.2)